Tolerance to desiccation and production of encapsulated units of gabiroba (Campomanesia adamantium) seeds - Braga, Valéria Prado; Silva, Andréia Vanessa da; Dias, Lana Laene Lima; Reis, Edésio Fialho dos; Machado, Carla Gomes; Costa Netto, Antônio Paulino da; Rocha, Diego Ismael (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
Campomanesia adamantium is a Brazilian Cerrado fruit crop species that presents a recalcitrant behavior, which compromises the viability of its seeds. Due to this seed feature, the objective of this study was to evaluate the preservation capacity of the species by the use of synthetic seeds. Two seed lots were maintained in a ventilation oven regulated at 30 °C for 30, 60, 120, 240 and 960 min, and then compared with the fresh seeds (control). After drying, the lots were evaluated according to the germination rate, emergence speed index (ESI), initial time, final time and mean time of germination, synchrony, relative frequency, germination speed and seed vigor. For the production of encapsulated units, 3 complexation times (15, 20 and 30 min) and 5 concentrations of sodium alginate (0, 1.5, 2, 2.5 and 3 g) were evaluated, with 3 replicates. For both experiments, Sisvar software was used, and the means were compared by Tukey test at 5%. Seed quality was compromised by desiccation, as the ESI decreases with increasing desiccation time. Regarding synchrony, there was no significant difference among the treatments, whereas for germination time, fresh seeds started and finished the process faster than the others, and the germination time increased as the drying treatments time increases. The emergence rate of fresh seeds was much higher than those exposed to desiccation. For synthetic seeds, the best complexation time was 20 min for 1.5, 2 and 3 g alginate, reaching 100% of the germinated encapsulated units. Index terms: Cerrado fruit crop; recalcitrant seeds; seed germination; synthetic seeds.